Using the Pair Check to Improve the Ability to Determine the Structure of Exposition Texta of Class VIII Students of SMP Negeri Wajo - Muliana, Hanana (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to improve the ability of class VIII students at MTs Pesantren Mizanul ’Ulum Sanrobone in learning to determine the structure of exposition text using the pair checks model, totaling 14 students. Data collection was carried out using test techniques. The money data obtained was analyzed using descriptive methods. This type of research is classroom action research which consists of two cycles, namely cycle I and cycle II. Which aims to describe the increase in the ability to determine the structure of exposition text using the pair checks model. Researchers only focused on class I with 14 students. The learning outcome for determining the structure of exposition text in cycle I was 65 and the student learning outcome for cycle II was 87.14. Based on the research results , it can be concluded that the learning outcomes of determining the structure of exposition text for class VIII SMP Negeri 2 Wajo can be improved by using the pair check model